Avaliação da Política Nacional de Atenção Cardiovascular de Alta Complexidade com foco na cirurgia cardiovascular pediátrica - Pinto Júnior, Valdester Cavalcante (2010)
The National Cardiovascular Care High Complexity Policy, focusing on Pediatric Cardiovascular Surgery, formalized on June 15, 2004, through Ordinance Nº. 1169/GM Nº and 210 SAS / MS is fomented by the intervention from the SBCCV and DCCVPed together with the Ministry Health and aims to meet the demand in pediatric cardiovascular surgery. At the time of the formulation the deficits in surgeries were expressive, being more critical in the North and Northeast. The research aims to evaluate the policy on its design, implementation and results. We used quantitative methods for analysis of primary data from questionnaires administered to surgeons and secondary collected from the MS / DATASUS and IBGE. The time frame was 1999 to 2008 for procedures in congenital heart disease and from 2001 to 2008 for the valve procedures. The qualitative analyses were used for the entrances and speeches by corporate directors and managers of MS. Analyses were buoyed on the premises of the National Health System, as fairness, integrity and regionalization in the light of some authors. The results have proved to be a landmark policy by recognizing the characteristics and particular needs in the area. However, there is lack of measures to improve the frequency of the procedures, still with significant deficits, 62% for Brazil and 91%, 76%, 55%, 36% and 47% for the north, northeast, southeast, south and central west respectively, and resolve regional inequities. Politics is, according to the the analysis employed, ineffective and inefficient. As strategies to support governance actions met: realign payment amounts per procedure; implement database in partnership with DCCVPed; tables reconcile the diagnostic procedures with the orthesis and prosthesis, identify centers of excellence in complex heart and set them as reference regional centers to sponsor professional training value fees, subsidize the restructuring of the institutions empowered and structuring those who enter the system, establish policy for regional equity, create Program Prevention and Control of Rheumatic Fever. In sum, it means the policy as a trigger of a process of structuring and continuous evaluation that will provide input and be a tool to persuade the powers that be.